THE URGENCY OF AMENDING THE LAW ON GOVERNING ACEH (LoGA) FROM THE ASYMMETRIC DECENTRALIZATION PERSPECTIVE - Mukhlis Mukhlis; M Nazaruddin (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
The issue of amending Law Number 11 of 2006 concerning Aceh Government is closely related to adjustments to changes in other laws and regulations that have an impact on the implementation of the LoGA. Therefore, efforts to amend the Law On Governing Aceh (LoGA) have become a necessity and problematic. In addition, it is also related to the need to strengthen the regulation on the sustainability of special autonomy funds for Aceh proposed at 2.5% of the National General Allocation Fund to continue development and improve the welfare of the people of Aceh for an indefinite period of time. On the other hand, a more detailed regulation is also needed within the proposed changes to the UUPA to facilitate its implementation in the field so that the authority of the Aceh government in implementing its special and privileged rights in the context of asymmetric decentralization can be better implemented.Isu perubahan Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh erat terkait dengan penyesuaian terhadap perubahan peraturan perundang undangan lainnya yang berdampak terhadap implementasi UUPA tersebut karena itu upaya perubahan terhadap UUPA menjadi suatu keniscayaan dan problematis, di samping terutama hal itu juga terkait dengan diperlukannya memperkuat keberadaan pengaturan tentang keberlanjutan dana otonomi khusus Aceh yang diusulkan sebesar 2,5 % dari flafon Dana Alokasi Umum Nasional untuk melanjutan pembangunan dan meningkatkan kesejahteraan rakyat Aceh untuk waktu yang tidak terbatas. Di sisi lain juga diperlukan pengaturan yang lebih rinci di dalam UUPA usulan perubahan ini untuk lebih mudah dalam pelaksanaannya di lapangan sehingga kewenangan Pemerintah Aceh dalam melaksanakan hak kekhususan dan istimewaannya dalam rangka desentralisasi asimetris lebih dapat diimplementasikan.